Ionizing radiation‐induced acoustics for radiotherapy and diagnostic radiology applications. Issue 7 (18th May 2018) - Hickling, Susannah; Xiang, Liangzhong; Jones, Kevin C.; Parodi, Katia; Assmann, Walter; Avery, Stephen; Hobson, Maritza; El Naqa, Issam
Abstract : Acoustic waves are induced via the thermoacoustic effect in objects exposed to a pulsed beam of ionizing radiation. This phenomenon has interesting potential applications in both radiotherapy dosimetry and treatment guidance as well as low‐dose radiological imaging. After initial work in the field in the 1980s and early 1990s, little research was done until 2013 when interest was rejuvenated, spurred on by technological advances in ultrasound transducers and the increasing complexity of radiotherapy delivery systems. Since then, many studies have been conducted and published applying ionizing radiation‐induced acoustic principles into three primary research areas: Linear accelerator photon beam dosimetry, proton therapy range verification, and radiological imaging. This review article introduces the theoretical background behind ionizing radiation‐induced acoustic waves, summarizes recent advances in the field, and provides an outlook on how the detection of ionizing radiation‐induced acoustic waves can be used for relative and in vivo dosimetry in photon therapy, localization of the Bragg peak in proton therapy, and as a low‐dose medical imaging modality. Future prospects and challenges for the clinical implementation of these techniques are discussed.